Elevation of a patient’s trunk and legs does not influence length of stay in the postanesthesia care unit - Omati, Otávio; Benseñor, Fábio Ely Martins; Vieira, Joaquim Edson (São Paulo Medical Journal, 2004)
CONTEXT: Patient recovery time after anesthesia depends on problem-oriented monitoring and individual assessment. OBJECTIVE: To investigate the influence of patient positioning on post-anesthesia recovery time. TYPE OF STUDY: Retrospective. SETTING: Post-anesthesia care unit, Hospital das Clínicas, São Paulo. METHODS: Data were obtained from patients recovering from anesthesia in a supine horizontal position or with their trunk and legs elevated at 30 degrees. Data were recorded every 30 minutes. The start time was considered to be the admission to the unit, and the final measurement was taken when the patient reached an Aldrete-Kroulik index of 10. The length of time until discharge was recorded. RESULTS: 442 patients recovering after general (n = 274) or regional anesthesia (n = 168) were assigned to be kept in a supine position or with their trunk and legs elevated. There was no difference in the medians for non-parametric results, between supine position (75 min, n = 229) and trunk and legs elevated (70 min, n = 213); p = 0.729. Patients recovered faster from regional anesthesia with trunk and legs elevated (70 min) than in the supine position (84.5 min), although not significantly (p = 0.097). There was no difference between patients recovering from general anesthesia, no matter the positioning (70 min; p = 0.493). DISCUSSION: Elevated legs may supposedly improve venous return and cardiac output since spinal anesthesia blocks sympathetic system and considering leg-raising has been shown to improve cardiac output from hipovolemia. Our findings did not support this hypothesis. Some limitations included a retrospective collection of data that did not allow randomization for recovery position and the unregistered duration of the exposure to the anesthetic drugs. CONCLUSIONS: There was no difference in anesthesia recovery time in relation to positioning patients supinely or with trunk and legs elevated.